Visible-Light-Induced C-3 Difluoroalkylation of Quinoxalin-2(1H)-ones with Difluoroiodane(III) Reagents under Catalyst-Free Conditions - Qin, Haijuan; Zhou, Ningning; Wang, Kun; Zhang, Ying; Zhao, Xia; Lu, Kui (Synlett, 2023)
A visible-light-induced radical difluoroalkylation of quinoxalin-2(1H)-ones by hypervalent-iodine-based reagents was developed. To facilitate the final oxidative step, [bis(trifluoroacetoxy)iodo]benzene (PIFA) was employed as an oxidant. Moreover, a one-pot protocol for this transformation was realized by generating the difluoroalkylation reagent in situ. The readily accessible reagents and the mild reaction conditions make this reaction an alternative and practical strategy for the synthesis of C(3)-difluoroalkylated quinoxalin-2(1H)-ones.
Keywords: difluoroalkylation; quinoxalinones; hypervalent iodine reagents; photocatalysis; catalyst-free reaction